Uporaba Edinburške lestvice poporodne depresije za presejanje očetov na poporodno depresijo - Karić, Anel (Obzornik zdravstvene nege, 2022)
Introduction: International research shows that approximately 10% of new fathers develop symptoms of postpartum depression in 4–6 months postnatal. The purpose of the research was to evaluate whether the adapted and translated version of Edinburgh Postpartum Depression Scale is reliable enough for screening postpartum depression of new fathers. Methods: Quantitative study was conducted. Using the adapted Edinburgh Postnatal Depression Scale we interviewed fathers with 4–6 month old infants during the visit of a community health nurse. The sample included all suitable candidates in Ljubljana - Črnuče and Velenje community health centres between August and December 2019 (n = 80), sample realisation was 51 (63%). The Cronbach alpha coefficient was 0.931. The chi-square test was used for analysing data. Results: Eight participants (15.7%) gathered score of 12 or more and were, therefore, at risk of developing postnatal depression. None of the respondents reported on having suicidal thoughts or intentions. The number of average achieved points was 6.76 (s = 3.99). The largest number of total points was 16 collected by one respondent (n = 1, 1.96%). Discussion and conclusion: Despite the small sample, which prevents a generalization of study results, the findings of our pilot study conclude that the proportion of Slovenian new fathers at risk of developing postpartum depression is similar to those in foreign studies. The recommendation of the study is to pay more attention to the mental health of new fathers, especially in the first year postpartum, since their well-being may also affect other family members.
Keywords: moški; poporodna depresija